2012
DOI: 10.1017/s136898001200362x
|View full text |Cite
|
Sign up to set email alerts
|

Birth weight and obesity risk at first grade of high school in a non-concurrent cohort of Chilean children

Abstract: Objective: To determine the association of birth weight with obesity risk at first grade of high school in Chilean children after accounting for potential confounding factors. Design: National non-concurrent cohort of newborns. Sociodemographic information, height, weight and anthropometric measurements at first grade of high school were analysed. Birth weight was classified as macrosomia ($4000 g), by gestational age and by ponderal index. The relationship between birth weight and obesity at first grade of hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
26
0
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 30 publications
4
26
0
4
Order By: Relevance
“…Most past studies have found a significant and positive association between birth weight and childhood obesity risk. [7][8][9][10][11][12][13][14][15][16][17][18][19] A population-based cohort study from Denmark indicated an increased risk of overweight for children 6-13 years of age with birth weight ⩾ 4.0 kg compared with those with birth weight between 3.0 and 3.49 kg. 12 Another Chinese birth cohort found that children with higher birth weight ⩾ 3500 g had an increased odds of childhood overweight at 3-6 years of age compared with those having birth weight of 3000-3249 g. 15 A meta-analysis of 66 studies from 26 countries demonstrated that high birth weight (44000 g) was positively associated with increased odds of childhood overweight (OR 1.66; 95% CI: 1.55-1.77) compared with normal birth weight (2500-4000 g).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most past studies have found a significant and positive association between birth weight and childhood obesity risk. [7][8][9][10][11][12][13][14][15][16][17][18][19] A population-based cohort study from Denmark indicated an increased risk of overweight for children 6-13 years of age with birth weight ⩾ 4.0 kg compared with those with birth weight between 3.0 and 3.49 kg. 12 Another Chinese birth cohort found that children with higher birth weight ⩾ 3500 g had an increased odds of childhood overweight at 3-6 years of age compared with those having birth weight of 3000-3249 g. 15 A meta-analysis of 66 studies from 26 countries demonstrated that high birth weight (44000 g) was positively associated with increased odds of childhood overweight (OR 1.66; 95% CI: 1.55-1.77) compared with normal birth weight (2500-4000 g).…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Several studies have indicated that high birth weight is associated with an increased risk of childhood obesity. [7][8][9][10][11][12][13][14][15][16][17][18][19] However, few studies have examined the extent to which birth weight is associated with obesity in young school children in high-, middle-and low-income countries. Moreover, the association between low birth weight and the risk of childhood obesity is controversial.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, several studies have reported that intrauterine growth retardation is associated with an increased prevalence for development of adult diseases such as cardiovascular and metabolic derangements (Fall et al, 1995;Godfrey & Barker, 2000); specifically, early growth failure (Singhal et al, 2003), and subsequent accelerated increase in weight gain and body mass index (BMI) during adolescence and adulthood (Bhargava et al, 2004;Loaiza & Atalah, 2012).…”
mentioning
confidence: 99%
“…This suggests that measures to prevent childhood obesity must begin at birth, or even before, as birth weight was found to predict obesity at age 14 years in 119 070 Chilean children adjusting for gender, age and mother's educational attainment at delivery (7) .…”
mentioning
confidence: 99%